The Influence of Ar Rahn Contract and Marketing Strategy on Customer Satisfaction at Pt. Sharia Pawnshop Margonda Branch, Depok - Damaiyanti, Ratih (IJBLE Scientific Publications Community Inc., 2025)
The objective of this research is to analyze the influence of the Ar Rahn contract and marketing strategies, transformed into the 7P Marketing Mix, on customer satisfaction at PT. Pegadaian Syariah Margonda Branch, Depok. The study involved 122 customers selected through a Simple Random Sampling technique using the Yount Table (1999) to determine the sample size. Data collection was conducted via questionnaires assessing Ar Rahn contract factors, marketing strategy, and customer satisfaction. Analytical tools included Classical Assumption tests, multiple linear regression, and hypothesis testing using t-statistics and F-statistics. The findings indicate that: (1) The Ar Rahn contract significantly influences customer satisfaction, with tvalue 47.502 > ttable 1.980 and significance value 0.001 < 0.05. (2) The 7P Marketing Mix significantly affects customer satisfaction, with tvalue 53.298 > ttable 1.980 and significance value 0.000 < 0.05. (3) The Ar Rahn contract and the 7P Marketing Mix simultaneously have a significant impact on customer satisfaction, with Fvalue 1554.974 > Ftable 3.07 and significance value 0.001 < 0.05.